The relationship between smoking status and smoking cessation practice for health workers in Surabaya - Kurnia D. Artanti; Santi Martini; Mahmudah Mahmudah; Sri Widati; Diva Adila; Muhammad A. Rahman (AOSIS, 2023)
Background: Indonesia is one of the countries that have a high smoker prevalence globally. Therefore, a smoking cessation program is key to reducing the smoking prevalence in Indonesia. The role of health workers is necessary for smoking cessation programs. However, smoking behavior among health workers could limit smoking cessation practices for patients. Objective: This study aims to analyze smoking behavior and 5A smoking cessation (Ask, Advice, Assess, Assist, and Arrange) practices among health workers. Materials and Methods: This study design is cross-sectional with a simple random sampling from the population of health workers in Surabaya. The total sample of this study counted 60 health workers. The data were analyzed in univariate and bivariate using SPSS 18 application. Bivariate analysis using a chi-square or Fisher exact test was conducted to analyze the relationship between smoking status and 5A smoking cessation practice. Results: Report of main outcomes or findings, including (where relevant) levels of statistical significance and confidence intervals. The result of this study shows that the asking practice was the most practiced item in the 5A model among health workers (98.3%). There was no significant association between smoking behavior and 5A implementation among health workers (PR=0.40; 95%CI: 0.52-5.30; P=1.67). Conclusions: There was no significant association between respondents' characteristics, smoking cessation training, and professional roles with 5A implementation.